Neuroscience Organizational Behavior for Employee Development Program - Anne Gracia Rachel Kaliey; Rivo Panji Yudha (Journal of Public Health Indonesian, 2025)
In the era of digital transformation, global organizational dynamics have become increasingly complex, highlighting the misalignment between human resource management and neurocognitive adaptability. Conventional management approaches often overlook the role of brain functions in influencing employee behavior and decision-making. This study explores organizational behavior through a neuroscience lens to identify behavioral patterns that can inform effective employee development programs. A qualitative exploratory case study design was employed, involving ten informants comprising HR managers, unit heads, and operational staff from a technology-driven service company. Participants were selected using purposive sampling based on criteria such as work experience and managerial involvement. Data were collected through semi-structured interviews, participant observation, and organizational document analysis. Thematic analysis was conducted through a six-phase process: data familiarization, initial coding, theme identification, theme review, theme definition, and report generation. Data validation was ensured through triangulation, peer debriefing, and member checking. The analysis yielded six key themes: (1) Work experience as a cognitive foundation, where senior employees demonstrated quicker and more intuitive decision-making; (2) Adaptive organizational behavior, characterized by flexible task allocation and informal team collaboration; (3) Varying effectiveness of managerial interventions, dependent on clarity and contextual relevance; (4) Awareness of the importance of neurocognitive profiling, yet lack of formal assessment implementation; (5) Hierarchical dynamics in decision-making, with senior staff often dominating discussions; and (6) Emotional and social support as crucial elements of team resilience. These findings underscore the gap between cognitive awareness and the systemic integration of neuroscience in organizational practice. Neuroscience offers a compelling framework for understanding and managing organizational behavior. Integrating neurocognitive profiling into human resource strategies has the potential to improve decision-making, team dynamics, and the precision of intervention programs. The study recommends developing brain-based assessment systems to foster adaptive, evidence-driven, and personalized workforce management in evolving organizational settings.